HUBUNGAN ANTARA SELF CONCEPT UNTUK BELAJAR MATEMATIKA dan BERFIKIR KREATIF DALAM MENYELESAIKAN MASALAH PROGRAM LINEAR - Fitrea Ananda; Mohammad Rifat; Dian Ahmad (Institut Pendidikan Tapanuli Selatan, 2023)
This study aims to explore the relationship between students' self-concept and creative thinking in solving program problems in a linear manner. The research method used is descriptive quantitative. This study involved 29 class XI students of SMAN Muhammadiyah 1 Pontianak using data collection techniques in the form of tests and questionnaires. The test questions consist of 4 sub-problems and 16 stands in the self-concept questionnaire. The data analysis technique uses the product moment correlation test. The results of rcount = -0.095 and rtable = 0.367 means that there is no significant relationship between self-concept and creative thinking. The higher the student's self-concept, the lower the creative thinking and conversely the lower the self-concept, the higher the ability to think creatively.